Clinical Profile and Treatment Evaluation of Rifampicin-Resistant and Multidrug-Resistant Tuberculosis Patients at Dr. Kanujoso Djatiwibowo Public Hospital, Balikpapan - Randy Adiwinata; Josephine Rasidi; Maurits Marpaung (Jurnal Respirologi Indonesia, 2018)
Background: Rifampicin-resistant (RR-TB) and multidrug-resistant tuberculosis (MDR-TB) remains a major health problem worldwide and in Indonesia also become a challenge in total eradication of tuberculosis. Dr. Kanujoso Djatiwibowo Public Hospital (RSKD) Balikpapan is one of the two referral hospitals in East Kalimantan for evaluation and initiation of MDR-TB treatment. The objective of this study is to evaluate clinical profile and treatment of RR-TB and MDR-TB patients at RSKD. Methods: A retrospective cross-sectional study was conducted using data from eTB manager database and medical record of RR-TB and MDR-TB at RSKD from January 2013 to October 2016. Results: Twenty eight RR-TB and MDR-TB patients, most of them were female (53.6%), belong to 35-44 age group (28.6%), housewife (25%), graduated from senior high school (42,9%), malnutrition (28.6%), and relapse cases (50%). Diabetes mellitus and anemia were found in 42,9% and 44.4% of the patients, respectively. The most resistant pattern is rifampicin-resistant TB (57,1%) followed by rifampicin and isoniazid resistant. The most common side effect of TB treatment was gastrointestinal complaints (44.4%). The success rate of MDRTB treatment at RSKD was 20%, followed by 20% mortality, 50% of lost to follow up, 10% of treatment failure, and there are 8 patients still ongoing therapy. Conclusion: Most of the RR-TB and MDR-TB cases were relapse cases. Counseling, education, and support for the patients undergoing MDR-TB treatment are strongly needed to increase success rate and decreasing number of lost to follow up.